Chondro-Protective Effects of Shikimic Acid on Osteoarthritis via Restoring Impaired Autophagy and Suppressing the MAPK/NF-κB Signaling Pathway - You, Hongbo; Zhang, Rui; Wang, Lingying; Pan, Qiyong; Mao, Zekai; Huang, Xiaojian (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a major cause of cartilage pain and limited mobility in middle-aged and elderly individuals. The degeneration of cartilage induced by inflammation and cartilage anabolic and catabolic disorder plays a key role in OA. Shikimic acid (SA), a natural ingredient extracted from Illicium verum, has been shown to exert notable anti-inflammatory effects in previous studies, suggesting its potential usefulness in the treatment of OA. In this study, we revealed that the pretreatment of SW1353 human chondrocytes with SA before interleukin 1β(IL-1β) stimulation effectively decreased the expression of inducible nitric oxide synthase (iNOS), cyclooxygenase (Cox)-2, matrix metalloproteinases (MMPs; MMP3 and MMP13), a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-5, type X collagen, and p62; increased the expression of type II collagen, ATG7, Beclin-1 and LC3; and increased autophagy flux. Mechanistically, we found that SA suppressed the IL-1β-induced activation of the mitogen-activated protein kinase (MAPK) and nuclear factor-kappaB (NF-κB) pathways. Furthermore, the results of safranin O staining and toluidine blue staining of primary rat cartilage chondrocytes and a trauma-induced rat model of OA showed that SA alleviated progression of OA in vivo. Collectively, our research enhances understanding of the mechanism of protective effect of SA against the progression of OA, which involves amelioration of cartilage degeneration, thereby providing new evidence for the use of SA as a therapy to prevent the development of OA.